IMPLEMENTASI IMPLEMENTASI TOILET TRAINING DALAM MEMBANGUN KEMANDIRIAN ANAK DI TAMAN PENITIPAN ANAK BUAH HATI KITA KABUPATEN JEMBER - Nia, Nia Rahmaningtyas; Purnamawati, Frimha; Yulianti, Nanik (Jurnal Empowerment, 2025)
This study aims to describe the implementation of toilet training in building children's independence in the "Buah Hati Kita" Child Care Park, Jember Regency. In this study, researchers used a type of descriptive research with a qualitative approach. This research was conducted at the "Buah Hati Kita" Child Care Park, Jember Regency. Data collection is done through interviews, observation, and documentation. The research subjects in this study were educators, principals, and parents and in determining informants using purposive sampling. The results showed that the implementation of toilet training has been carried out well in increasing children's independence in the "Buah Hati Kita" Child Care Park. Where the child's independence is seen through the physical ability shown by the child to go to the toilet by himself, take off and put on their own pants or skirt, and the ability to squat, meanwhile, confidence is shown by the child in communicating the desire to defecate, for responsibility is shown the child the habit of urinating or defecating in the bathroom, cleaning feces (cebok) as well as the habit of flushing the toilet and discipline shown by the child through accustoming the child not to wearing diapers. Although well carried out, there are some activities that still do not lead to the process of independence. But educators and parents will train children step by step to be able to support independence in the toilet. Toilet training is important for children, therefore toilet training must be programmed in various institutions that shelter early childhood, especially in Child Care Parks. Child Care Park which serves to provide educational services and welfare guidance for early childhood in order to grow and develop optimally. So a toilet training program is needed that can form independence in children. Keywords: toilet training, child independence, daycare park